Hormonal contraception and the risk of HIV acquisition - Charles S. Morrison (2018)
BACKGROUND: Combined oral contraceptives (COC) and depot- medroxyprogesterone acetate (DMPA) are among the most widely used family planning methods; their effect on HIV acquisition is not known. OBJECTIVE: To evaluate the effect of COC and DMPA on HIV acquisition and any modifying effects of other sexually transmitted infections. METHODS: This multicenter prospective cohort study enroled 6109 HIV-uninfected women, aged 18-35 years, from family planning clinics in Uganda, Zimbabwe and Thailand. Participants received HIV testing quarterly for 15-24 months. The risk of HIV acquisition with different contraceptive methods was assessed (excluding Thailand, where there were few HIV cases). RESULTS: HIV infection occurred in 213 African participants (2.8/100 woman-years). Use of neither COC [hazard ratio (HR), 0.99; 95% confidence interval (CI), 0.69-1.42] nor DMPA (HR, 1.25; 95% CI, 0.89-1.78) was associated with risk of HIV acquisition overall, including among participants with cervical or vaginal infections. While absolute risk of HIV acquisition was higher among participants who were seropositive for herpes simplex virus 2 (HSV-2) than in those seronegative at enrolment, among the HSV-2-seronegative participants, both COC (HR, 2.85; 95% CI, 1.39-5.82) and DMPA (HR, 3.97; 95% CI, 1.98-8.00) users had an increased risk of HIV acquisition compared with the non-hormonal group. CONCLUSIONS: No association was found between hormonal contraceptive use and HIV acquisition overall. This is reassuring for women needing effective contraception in settings of high HIV prevalence. However, hormonal contraceptive users who were HSV-2 seronegative had an increased risk of HIV acquisition. Additional research is needed to confirm and explain this finding. © 2007 Lippincott Williams & Wilkins, Inc.